Occupational low back pain in nursing workers: massage versus pain - Talita Pavarini Borges; Leonice Fumiko Sato Kurebayashi; Maria Júlia Paes da Silva (SciELO, 2014)
Objective: To assess the efficacy of massage for decreasing occupational low back pain in workers of a Nursing team in an Emergency Room. Method: A randomized controlled trial, using a socio-demographic/morbidity questionnaire and a Pain Numeric Scale. Forty-five subjects were randomly allocated for intervention (G1 - Massage by acupressure), placebo group (G2 - application of Garlium Arseneid Laser 904nm turned off) and control (G3 - no intervention). Results: The main triggering factor, as well as the worsening of pain, was the patient manipulation, both with a prevalence of 34.9%. The main treatment for low back pain before this research was the use of medication, with a prevalence of 44.2%. In accordance with a variance analysis, only G1 presented a significant statistical difference, with a better result after 12 sessions. Massage presented an enormous effect (d = 4.59), corresponding to 86% of reduction in the pain level. Conclusion: Massage was effective to decrease occupational low back pain of those Nursing workers.